2019
DOI: 10.1007/s40261-019-00778-5
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Rechallenge After Other Targeted Therapies in Metastatic Renal Cell Carcinoma Patients: A Single-Center, Retrospective Study

Abstract: Background Sunitinib is still one of the standard therapies in metastatic renal cell carcinoma (mRCC). Despite the benefit of sunitinib resistance will develop in the majority of patients. Most of them receive multiple sequential therapies during the course of disease. Objectives To retrospectively investigate the efficacy and safety of rechallenged sunitinib in third or later line settings. Patients and Methods Twenty-one mRCC patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…First, median PFS on Sunitinib rechallenge is higher than usually observed with the same agent in large phase III studies conducted in the first-line setting, that is, between 8.3 and 11.1 months; 28 33 even longer as compared to what was expected is the overall survival of our case series. Of course, it is clear that our patient population was highly biased, having shown particular sensibility to VEGFR inhibition (patients, by protocol, had to have had a disease control of at least 10 months in first line) and having survived enough to reach a third-line (or even more) treatment still in good conditions.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…First, median PFS on Sunitinib rechallenge is higher than usually observed with the same agent in large phase III studies conducted in the first-line setting, that is, between 8.3 and 11.1 months; 28 33 even longer as compared to what was expected is the overall survival of our case series. Of course, it is clear that our patient population was highly biased, having shown particular sensibility to VEGFR inhibition (patients, by protocol, had to have had a disease control of at least 10 months in first line) and having survived enough to reach a third-line (or even more) treatment still in good conditions.…”
Section: Discussioncontrasting
confidence: 44%
“…Indeed, most data on sunitinib re-challenge came from retrospective studies, small case series, or even single case reports, 14,[19][20][21][22][23][24][25] constantly showing activity, efficacy, as well as tolerability. Of note, in few patients, PFS was longer following re-challenge than with initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies, sunitinib re-challenge, and sequential therapy have been investigated to overcome resistance to sunitinib [ 2 , 36 , 37 , 38 ]. We further tested an optimized multidrug combination consisting of four tyrosine kinase inhibitors, AZD4547, osimertinib, AZD8055 and pictilisib [ 37 ], to reveal whether acquired resistance to sunitinib can be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results obtained from experiments in mice had already suggested that RCC tumours could still re‐gain sensitivity to sunitinib or sorafenib after failed response or resistance to the same drugs [37,38]. In this sense, re‐introduction of sunitinib as second‐, third‐ or subsequent lines of therapy after RCC progression has proven efficacy [39–43]. All these results suggested that changes in the tumour microenvironment or temporal breaks between treatments could favour the re‐gain of tumour sensitivity to targeted therapy.…”
Section: Discussionmentioning
confidence: 96%